COMPARISON OF LATENT MOTOR DIMENSIONS BETWEEN 11 YEAR-OLD SCHOOL BOYS AND GIRLS - Georgi Georgiev (Sport Mont, 2008)
This research is realised on a sample of 500 entities (250 school boys and 250 school girls) aged 11. They were treated with 21 motor tests in order to be determined and compared their motor structures. Along with basic statistic parameters a factor analyse is applied (promax rotation). Comparison of the structures between the schoolboys and school girls is determined by the Tucker’s coeffi cient of congruency. There are determined by 8 latent motor dimensions with the school boys and school girls, however Tucker’s coeffi cient has signifi cant value only between the second latent dimension with the male and the third latent dimension with the female.